Lack of the E3 Ubiquitin Ligase March1 Affects CD8 T Cell Fate and Exacerbates Insulin Resistance in Obese Mice - Majdoubi, Abdelilah; Lee, Jun Seong; Kishta, Osama A.; Balood, Mohammad; Moulefera, Mohamed Abdelwafi; Ishido, Satoshi; Talbot, Sébastien; Cheong, Cheolho; Alquier, Thierry; Thibodeau, Jacques (Frontiers in Immunology, 2020)
Obesity is a major risk factor for the development of insulin resistance and type 2 diabetes. However, the mechanisms that trigger the underlying adipose tissues inflammation are not completely understood. Here, we show that the E3 ubiquitin ligase March1 controls the phenotypic and functional properties of CD8+ T cells in mice white adipose tissue. In a diet-induced obesity model, mice lacking March1 (March1 KO) show increased insulin resistance compared to their WT counterparts. Also, in obese March1 KO mice, the proportions of effector/memory (Tem) and resident/memory (Trm) CD8+ T cells were higher in the visceral adipose tissue, but not in the spleen. The effect of March1 on insulin resistance and on the phenotype of adipose tissue CD8+ T cells was independent of MHC class II ubiquitination. Interestingly, we adoptively transferred either WT or MARCH1 KO splenic CD8+ T cells into obese WT chimeras that had been reconstituted with Rag1-deficient bone marrow. We observed an enrichment of Tem and Trm cells and exacerbated insulin resistance in mice that received March1 KO CD8 T cells. Mechanistically, we found that March1 deficiency alters the metabolic activity of CD8+ T cells. Our results provide additional evidence of the involvement of CD8+ T cells in adipose tissue inflammation and suggest that March1 controls the metabolic reprogramming of these lymphocytes.